New Sunday Times, 23 May 2010 - T.N. Alagesh (The New Straits Times Press (M) Bhd, 2010)
Tourists scaling this mountain never complain of tiredness. They talk about having a "good feeling" upon reaching the mountain's peak, and having a smile plastered on their faces.